1990
DOI: 10.1080/00288233.1990.10428458
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clovers in dry hill country 7. Subterranean and white clovers at Porangahau, Hawkes Bay, New Zealand

Abstract: Nine subterranean clover cultivars (Trifolium subterraneum L.) and 10 white clover lines(T. repens L.) wereevaluated for5 yearsunder conditions of regular summer drought and winter water-logging. Grazing management initially allowed an assessment of growth potential; regenerative ability was morerealistically assessed under typical farm management during the last 3 years of the experiment. Erect, open growing subterranean clover cultivars (e.g., 'Clare', 'Woogenellup') yielded the most under lenient cutting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…A similar conclusion was reached at other sites in this series (e.g., Macfarlane et al 1990;Sheath & Macfarlane 1990a;Sheath et al, 1990). The later plants flower, the greater their opportunity to exploit the warm, moist growth conditions of spring.…”
Section: Cultivar Performancesupporting
confidence: 64%
“…A similar conclusion was reached at other sites in this series (e.g., Macfarlane et al 1990;Sheath & Macfarlane 1990a;Sheath et al, 1990). The later plants flower, the greater their opportunity to exploit the warm, moist growth conditions of spring.…”
Section: Cultivar Performancesupporting
confidence: 64%
“…This cultivar was consistently cited in the national evaluation series as being the most well-adapted to dry North Island hill country environments Macfarlane et al 1990;Sheath & Macfarlane 1990a;Sheath et al 1990). In the previous two trials in the present series (Dodd et al 1995a,b), its suitability for this environment was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of these trials was to evaluate the persistence of a number of subterranean clover selections in a temperate, moderate-steep hill country environment. Desirable characteristics were identified in previous experiments (Sheath & Richardson 1983;Chapman et al 1986;Macfarlane et al 1990;Sheath & Macfarlane 1990a,b;Sheath et al 1990;Williams et al 1990). The screening programme included naturalised genotypes from long-term hill pastures in New Zealand, overseas accessions, and standard Australian cultivars.…”
Section: Introductionmentioning
confidence: 98%
“…The hill land environment, characterised by variable levels of soil mineral nutrients, spatially and temporally uneven soil moisture supply, and variable defoliation, creates strong selection pressure against poorly adapted plant material. Charlton (1984), Sheath et al (1990), Macfarlane et al (1990a-c) and Chapman & Williams (1990) all present evidence of poorly adapted white clover or subterranean clover (Trifolium subterraneum) lines being eliminated, or reduced to a bare presence in the sward, within 3 years of introduction.…”
Section: Introductionmentioning
confidence: 99%